Girdling promotes tomato fruit enlargement by enhancing fruit sink strength and triggering cytokinin accumulation - Chai, Lin; Wang, Heng; Yu, Hongjun; Pang, Endi; Lu, Tao; Li, Yang; Jiang, Weijie; Li, Qiang (Frontiers in Plant Science, 2023)
Girdling is a horticultural technique that enhances fruit size by allocating more carbohydrate to fruits, yet the underlying mechanisms are not fully understood. In this study, girdling was applied to the main stem of tomato plants 14 days after anthesis. Following girdling, there was a significant increase in fruit volume, dry weight, and starch accumulation. Interestingly, sucrose transport to the fruit increased while the fruit’s sucrose concentration decreased. Girdling also led to an increase in the activities of enzymes involved in sucrose hydrolysis and AGPase, and an upregulation in the expression of key genes related to sugar transportation and utilization. Moreover, the assay of carboxyfluorescein (CF) signal in detached fruit indicated that girdled fruits exhibited a greater ability to take up carbohydrates. These results indicate that girdling improves sucrose unloading and sugar utilization in fruit, thereby enhancing fruit sink strength. In addition, girdling induced cytokinin accumulation, promoted cell division in the fruit, and upregulated the expression of genes related to cytokinin synthesis and activation. Furthermore, the results of a sucrose injection experiment suggested that increased sucrose import induced cytokinin accumulation in the fruit. This study sheds light on the mechanisms by which girdling promotes fruit enlargement and provides novel insights into the interaction between sugar import and cytokinin accumulation.